Penatalaksanaan Fisioterapi Pada Kasus Bell’s Palsy - Hafiza Amalia; Agus Widodo; Muhammad Fauzan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Introduction: Bell's palsy is a peripheral paralysis of the seventh cranial nerve with unilateral and rapid onset. Bell's palsy is an idiopathic condition that causes partial or complete weakness of one half of the face accompanied by changes in taste, sensitivity to sound, and changes in lacrimation and salivation. In this case, the patient complained of pain when the left nostril was pressed and was unable to expand the nostrils symmetrically between right and left and was unable to close the left eye completely. Physiotherapy plays an important role in reducing the symptoms of bells palsy by providing infrared (IR), massage, mirror exercises. Objective: To determine the effectiveness of infrared (IR), massage, mirror exercise on bell's palsy. Method: Performed on a 49 year old patient who suffered from Bell's palsy. Results: Evaluation was carried out using Manuat Muscle Testing (MMT), Numeric Pain Rating Scale (NPRS), Ugo Fisch Scale. Conclusion: There is an increase in function in the form of increased muscle and functional strength and decreased pain.